PENEGAKAN HUKUM PIDANA TERHADAP PELAKU YANG MEMPERDAGANGKAN IKAN ARWANA (SCLEROPAGES FORMOSUS) TANPA IZIN DI KABUPATEN KAPUAS HULU SEBAGAIMANA DIATUR DALAM UNDANG-UNDANG NOMOR 5 TAHUN 1990 TENTANG KONSERVASI SUMBER DAYA ALAM HAYATI DAN EKOSISTEMNYA - DONI SAHRIZAL NIM. A1012171022 (Fakultas Hukum Universitas Tanjungpura, 2023)
ABSTRACT Arowana fish is a type of freshwater fish whose natural habitat is in nature and is included in the endangered species list. Arowana fish is a type of fish that is protected by legislation and currently its population is almost extinct. This arowana fish comes from the Kapuas Hulu Regency, West Kalimantan Province and has a high selling value because of its rarity. Therefore, many people in Kapuas Hulu Regency are trying to do Arowana fish breeding with the aim of trading it. To be able to trade captive Arowana fish, it is mandatory to have a BKSDA permit. However, in reality, there are still many breeders in Kapuas Hulu District who trade captive Arowana fish without having a permit from the West Kalimantan BKSDA.The formulation of the problem in this research is: